EXAMINING CEFR READING COMPREHENSION TEXT COMPLEXITY IN VIETNAM’S 2025 NATIONAL ENGLISH EXAM - Nguyen Thi Khanh An; Tran Trong Thanh (HNUE Journal of Science: Journal of Educational Science, 2026)
This study examines the complexity of reading comprehension passages in the English component of the 2025 National High School Graduation Exam. It estimates the CEFR-aligned difficulty levels of passages from the 2020-2025 examinations using quantitative measures and qualitative CEFR (Common European Framework of Reference for Languages) descriptors and compares them against the B1 benchmark specified in the national curriculum. The findings suggest a substantial increase in difficulty over time, with passages in the 2025 examination exhibiting complexity characteristics associated with C1-C2 levels in terms of lexical and readability demands. These levels considerably exceed the B1 requirement outlined in the 2018 General Education Curriculum. The results suggest a growing mismatch between curriculum standards and examination demands, raising concerns about validity, equity, and fairness. The study contributes to international discussions on high-stakes language testing by highlighting the importance of curriculum-assessment alignment and transparent test design in promoting pedagogical coherence and educational justice.